Recuperação de níquel e cobalto a partir de polpas de lixiviação ácida de minério laterítico pelo emprego de resinas poliméricas de troca iônica - Flavia Dutra Mendes (2005)
This work aimed at the selective extraction of nickel and cobalt, from high pressure acid leach discharge pulp of a Brazilian nickel laterite ore, through the application of ion exchange technique with polymeric resins. The proposed methodology consisted basically of six different stages. Firstly, some chelating commercial polymeric resins were evaluated (Dowex M4195®, Amberlite IRC748®, Ionac SR-5® and Purolite S930®). The resin Amberlite IRC748® presented the best results of nickel(2,13 mmol Ni/g) and cobalt (0,13 mmol Co/g) sorption from acidic solutions. Second stage consisted of a study of some process parameters, that have influence on nickel and cobalt selective sorption through the application of chelating resins, such as solution pH, alkali addition for pulp pH increase, temperature, resin/solution ratio and agitation. The next stage consisted of selective removal of nickel and cobalt from acidic impure solutions by applying column sorption with Amberlite IRC748®. The experimental results showed that lower flow rate values, higher pH and higher nickel concentration in the solution improved the performance of the ion exchanger, thus resulting in largerload nickel capacities. Later, resin- in-pulp batch tests were carried out in order to evaluate the nickel sorption performance of the chelating resin Amberlite IRC748® regarding its contact with high pressure acid leach discharge pulp. The results showed that it was achieved good nickel and cobalt recoveries from solution higher than 99% after five counter-current stages. Fifth stage consisted of a resin- in-pulp evaluation for nickel and cobalt sorption in a continuous scale using a chelating resin, defined in this text as CheRes, containing an iminodiacetic acid group. Three campaigns of 50 hours each were accomplished to evaluate the technical viability of resin- in-pulp process concerning nickel and cobaltrecovery from a Brazilian laterite ore. Finally, a characterization study of Amberlite IRC748® through Raman Spectroscopy was carried out for the evaluation of nickel species sorption onto the iminodiacetic acid functional group of the resin.